Compressive strength of concrete using glass powder as a filler replacement - Nur Shahira Diana , Salehuddin (2012)
A lot of researches have been done to improve the quality of concrete that can be used in long term period and design a more economic concrete for the construction. Using waste glass as a construction material is a good way to help the environment. The purpose of this study focused on the physical properties of concrete in terms of workability and compressive strength after added the glass powder as a sand replacement. 27 samples of concrete including control samples were prepared for this study. Concrete were designed based on grade 30 at a 28 days and water cement ratio is 0.55. Glass powder was used as a replacement material for sand in proportion 10 % and 20 %. Control samples are used as a guide and the result will be compared with the data of control samples. The average result of slump test for control samples is 30 mm in a range 30-60 mm The average value of compression test for control samples is 34.10 N/mm 2 at a 28 days and it's achieve the target value for concrete grade 30. The experimental results are compared with the control samples have the lower strength with the increasing of the glass powder that replace in sand. Average workability value for samples 10 % and 20 % is 115 mm and 120 mm respectively which is the higher workability. Concrete utilizing glass powder demonstrated a higher mod failure pattern with the lower strength that may caused from the Alkali Silica Reaction in concrete.